"That must be so hard"- Examining the impact of children's palliative care services on the psychological well-being of parents. (January 2013) - Gupta, Vineeta; Prescott, Helen
In 2003 the New Opportunities Fund (NOF, now known as The Big Lottery) awarded £48 million to 70 home-based care teams to enable them to provide a range of services to allow children with non-malignant life-limiting conditions to be cared for at home. Four grants were made available in Bristol, North Somerset, South Gloucestershire and Bath and North East Somerset to enhance existing children's palliative care services. As there is limited evidence about the impact of palliative care services on psychological well-being, this study measured parental stress and the psychological wellbeing of parents of newly referred children with life-limiting and life-threatening conditions. Measures were administered at the point of referral and at 12 months follow-up. Statistical analysis indicated that there was no significant change at 12 month follow-up. The lack of deterioration in levels of parental stress and psychological wellbeing is viewed positively within this context. It is hypothesised that multi-agency and partnership working was a significant contributory factor in not increasing levels of parental stress and psychological wellbeing through social support.